Modeling Energy Efficiency and Economic Growth: Evidences from India - Sinha, Avik (International Journal of Energy Economics and Policy, 2014)
India’s fossil fuel based energy-led economic growth has changed its pattern over a time and it is mainly driven by energy efficiency. In this paper, we have considered reduction in energy waste as a proxy of energy efficiency and analyzed its interplay with economic growth for 1971-2010. We have used Vector Error Correction model, and it has been seen that unidirectional causality exists from economic growth to energy waste, and this causal association is both short run and long run in nature. Moreover, energy waste is following a negatively elastic relationship with the economic growth along the energy efficiency frontier. Keywords: Economic Growth; Energy Waste; India, Vector error correction JEL Classifications: O44; Q42; Q43